Genetic manipulation in farmed fish: enhancing aquaculture production - Siraj, Siti Shapor (Universiti Putra Malaysia Press, 2011)
Ever since the creation of human civilisation, breeding has been the pivotal struggles to increase and diversify agricultural production, enhance food security and incomes, and adapt farming to changing environmental conditions and social needs. This is achieved by exploiting variation of the plant and animal genetic resources’ traits. These preferred genetic materials are improved through selection and reproduction and this practice remains the basis for producing new generations of domesticated and indigenous breeds. Aquatic organisms particularly finfish and shellfish that are cultured today originated largely from the introduction of scientific breeding at the beginning of the twentieth century. Inclusion of crosses into breeding schemes prior to artificial selection and application of Mendel’s laws of inheritance to improve both simple and quantitative traits follows. For effective breeding effort, selecting genetic materials with one or a combination of the required traits still relies mainly on physical features (phenotype) which are influenced by the environment thus could be misguided to the actual heritable genetic composition (genotype) of the material being considered. The extent of aquatic diversity is both extremely large and relatively poorly understood. Thus, identification, selection and estimation of specific traits (such as growth rate, disease resistance) in wild and cultured fish and shellfish through genetic tools and breeding programmes are a must to secure future improvements in genetic resources for food. Ever since the discovering of DNA structure over 50 years ago, scientists have made tremendous strides in identifying genes and gene functions, making it increasingly possible to detect genetic differences (DNA polymorphisms) for traits among individuals in a much more direct way, thereby assisting in the selection of desired traits. In fish, manipulation of the pre-embryonic stages rendering different ploidy levels is achievable and tolerable. Triploid fish is produced through various physical, chemical and biological stimulants. Triploids generally cannot reproduce, so the energy that is not channelled into reproduction would go instead to increasing growth rate. Induction of gynogenesis involves egg activation by irradiated homologous or heterologous sperm, and diploidization by retention of the second polar body (meiotic gynogenesis), or suppression of the first mitotic cleavage (mitotic gynogenesis). As a consequence, these gynogens are “instantly inbred” and can be screened for phenotypes quickly to avoid the generations of breeding necessary in a conventional manner. Artificial breeding is a simple genetic technology for forced reproduction such as the use of pituitary gland extract and other hormones to initiate gamete development and induce spawning (the release of fish eggs) besides triggering factors of the environment.